Upaya Peningkatan Kecerdasan Sosial Dan Emosional Anak Usia Dini Dalam Pendidikan Islam : Efforts To Improve The Social And Emotional Intelligence Of Young Children In Islamic Education - Pascalian Hadi Pradana Dewi Masyitoh (An-Nisa’ Journal of Gender Studies, 2018)
This qualitative research aims to describe the form and implementation of PAI in kindergarten schools and identify the impact of Islamic education on the social and emotional intelligence of early childhood. The research locations are PAUD/TK Al-Amin in Jember Regency, both of which are Islamic-based schools and favorite schools in Jember. The data collection methods used were interviews, observations, literature studies, and documentation studies with PAUD teacher representatives as informants. Meanwhile, data analysis followed the interactive model of qualitative data analysis, namely through the processes of Data Reduction, Data Displays, Conclusion Drawing/ Verification. The findings of this research indicate that the role of Islamic education is very important in efforts to develop children's social and emotional intelligence because it includes moral education and shapes children's moral character for the better, considering that children of this age are in their golden age. Islamic education must be instilled as early as possible in early childhood because it is very good for the growth and development of their personalities.